Beggar-Thy-Neighbour Tax Cuts: Mobility after a Local Income and Wealth Tax Reform in Switzerland - Isabel Z. Martinez (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Tax competition raises the question to which extent taxpayers respond to differences in income tax rates by migrating to low-tax areas. This paper analyzes a large, two-step tax reform in the canton of Obwalden in central Switzerland in 2006 and 2008. The canton first introduced a regressive income tax scheme with the explicit purpose of attracting affluent taxpayers, followed by a change to a flat rate tax, thereby lowering taxes for all taxpayers. Using individual tax data from the cantonal tax administration, I apply a 2SLS approach to estimate how responsive migration was to the tax reduction. I estimate an elasticity of the stock of rich taxpayers in the canton with respect to the average net-of-tax rate of 2.4 in the first two years after the reform, increasing to 3.5 over the five post-reform years. The corresponding elsticities of the inflow of rich taxpayers are even larger. These estimates are larger than what the few studies on tax induced mobility elasticity have found so far. I can further rule out that these results are due to an exogenous positive income shock to top incomes. DiD estimations comparing the share of rich taxpayers and net income per taxpayer in Obwalden to two neighboring cantons confirm that the reform was successful in increasing the canton's tax base. The large elasticities can be explained by two aspects. First, by the sizable pool of intentionally treated and the prevailing residence-based taxation, as opposed to source-based taxation. Through relocating to Obwalden, any Swiss and European citizen could take advantage of this tax scheme. Second, by the initially low share of rich taxpayers in Obwalden and the small size of the canton.
Keywords: H71; H24; H31; 330